DYNAMICS AND PREDATION EFFICIENCY OF CHRYSOPERLA EXTERNA (NEUROPTERA: CHRYSOPIDAE) ON ENNEOTHRIPS FLAVENS (THYSANOPTERA: THRIPIDAE) - Rodrigues, Camila Alves [UNESP]; Magalhaes Borges Battel, Ana Paula; Martinelli, Nilza Maria [UNESP]; Moral, Rafael De Andrade; Sercundes, Ricardo Klein; Conde Godoy, Wesley Augusto (Florida Entomological Soc, 2014)
The dynamics of predation by the green lacewing Chrysoperla externa Hagen (Neuroptera: Chrysopidae) on Enneothrips flavens Moulton (Thysanoptera: Thripidae) was investigated by placing embryonated eggs and first-instar larvae of C. externa on potted peanut plants (Arachis hypogaea L.; Fabales: Fabaceae) in a greenhouse. The plants that received either embryonated eggs or larvae of C. externa showed significant reductions in the mean numbers of thrips, about 9 days after the release of the predator on the plants. The potential of C. externa as a biological control agent for thrips is discussed.
Keywords: green lacewings; biological control; peanuts; predator performance